Macrofilaricidal efficacy of single and repeated oral and subcutaneous doses of flubendazole in Litomosoides sigmodontis infected jirds. - Marc P Hübner; Alexandra Ehrens; Marianne Koschel; Bettina Dubben; Franziska Lenz; Stefan J Frohberger; Sabine Specht; Ludo Quirynen; Sophie Lachau-Durand; Fetene Tekle; Benny Baeten; Marc Engelen; et al. (PLoS Neglected Tropical Diseases, 2019)
Flubendazole (FBZ) is highly efficacious against filarial nematodes after parenteral administration and presents a promising macrofilaricidal drug candidate for the elimination of onchocerciasis and other filariae. In the present study the efficacy of a newly developed bioavailable amorphous solid dispersion (ASD) oral formulation of FBZ was investigated in the Litomosoides sigmodontis jird model. FBZ was administered to chronically infected, microfilariae-positive jirds by single (40mg/kg), repeated (2, 6 or 15mg/kg for 5 or 10 days) oral (OR) doses or single subcutaneous (SC) injections (2 or 10mg/kg). Jirds treated with 5 SC injections at 10mg/kg served as positive controls, with untreated animals used as negative controls. After OR doses, FBZ is rapidly absorbed and cleared and the exposures increased dose proportionally. SC administered FBZ was slowly released from the injection site and plasma levels remained constant up to necropsy eight weeks after treatment end. Increasing single SC doses caused less than dose-proportional exposures. At necropsy, all animals receiving 1x or 5x 10mg/kg SC FBZ had cleared all adult worms and the 1x 2mg/kg SC treatment had reduced the adult worm burden by 98%. 10x 15mg/kg OR FBZ reduced the adult worm burden by 95%, whereas 1x 40mg/kg and 5x 15mg/kg OR reduced the worm burden by 85 and 84%, respectively. Microfilaremia was completely cleared at necropsy in all animals of the SC treatment regimens, while all oral FBZ treatment regimens reduced the microfilaremia by >90% in a dose and duration dependent manner. In accordance, embryograms from female worms revealed a FBZ dose and duration dependent inhibition of embryogenesis. Histological analysis of the remaining female adult worms showed that FBZ had damaged the body wall, intestine and most prominently the uterus and uterine content. Results of this study demonstrate that single and repeated SC injections and repeated oral administrations of FBZ have an excellent macrofilaricidal effect.